2021
DOI: 10.1126/science.abj4176
|View full text |Cite
|
Sign up to set email alerts
|

Durability of mRNA-1273 vaccine–induced antibodies against SARS-CoV-2 variants

Abstract: SARS-CoV-2 mutations may diminish vaccine-induced protective immune responses, particularly as antibody titers wane over time. Here, we assess the impact of SARS-CoV-2 variants B.1.1.7 (Alpha), B.1.351 (Beta), P.1 (Gamma), B.1.429 (Epsilon), B.1.526 (Iota), and B.1.617.2 (Delta) on binding, neutralizing, and ACE2-competing antibodies elicited by the vaccine mRNA-1273 over seven months. Cross-reactive neutralizing responses were rare after a single dose. At the peak of response to the second vaccine dose, all i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
385
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 503 publications
(430 citation statements)
references
References 33 publications
40
385
3
2
Order By: Relevance
“…Currently, all the licensed vaccines have been designed to elicit immune responses to the spike protein for providing protection, therefore, it is reasonable for the assumption that the patterns of neutralizing antibody responses post-vaccination will follow the patterns seen in post-infection follow-up 67,68 . Some recent studies suggested both the binding and neutralizing antibody responses possessed similar rate of decline between vaccination of mRNA vaccine or infection during the first 7 months after vaccination 69,70 , and our study provide further hints for the durability assessment of vaccine induced antibody response. Furthermore, individuals previously diagnosed with COVID-19 could develop potent humoral immunity rapidly after a single dose of mRNA vaccine [71][72][73] .…”
Section: Discussionsupporting
confidence: 69%
“…Currently, all the licensed vaccines have been designed to elicit immune responses to the spike protein for providing protection, therefore, it is reasonable for the assumption that the patterns of neutralizing antibody responses post-vaccination will follow the patterns seen in post-infection follow-up 67,68 . Some recent studies suggested both the binding and neutralizing antibody responses possessed similar rate of decline between vaccination of mRNA vaccine or infection during the first 7 months after vaccination 69,70 , and our study provide further hints for the durability assessment of vaccine induced antibody response. Furthermore, individuals previously diagnosed with COVID-19 could develop potent humoral immunity rapidly after a single dose of mRNA vaccine [71][72][73] .…”
Section: Discussionsupporting
confidence: 69%
“…1b). Of note, we performed this assay in all 46 volunteers in Vero-E6 cells to compare with the data we reported recently 6 and all the previous studies where we used this assay 5,[7][8][9] . The durability of neutralizing titers against the homologous strain was comparable to that of the responses in mRNA1273 vaccinees 5,10 .…”
mentioning
confidence: 63%
“…1 However, the emergence of SARS-CoV-2 variants of concern (VOCs) raises questions about the specificity and potential cross-protection mediated by these antibodies. While antibody responses have been extensively studied for vaccinee sera, 2 human milk antibodies – a major contributor to passive immunity for infants – have not been analyzed.…”
Section: Objectivementioning
confidence: 99%